Iron Oxide Nanoclusters Incorporated into Iron Phthalocyanine as Highly Active Electrocatalysts for the Oxygen Reduction Reaction. Issue 2 (15th December 2017) - Cheng, Yi; Liang, Ji; Veder, Jean‐Pierre; Li, Meng; Chen, Shuangming; Pan, Jian; Song, Li; Cheng, Hui‐Ming; Liu, Chang; Jiang, San Ping
Abstract: Iron‐nitrogen‐carbon (Fe‐N‐C) composites have emerged as active and non‐precious‐metal electrocatalysts for the oxygen reduction reaction (ORR). Here, we developed a simple process to synthesize FeO x nanoclusters (NCs) incorporated with iron phthalocyanine (FePc) supported on graphene (FeO x /FePc) as highly active electrocatalysts for the ORR by a self‐assembly method. The electrochemical activity of FeO x /FePc depends on the loading or size of the FeO x NCs. The best results are obtained on FeO x /FePc with 10 wt % FeO x NCs of a size of approximately 2 nm and a thickness of approximately 0.6 nm, which achieves a half‐wave potential of 0.888 V and current density of 37.6 Ag −1 at 0.9 V (vs. the reversible hydrogen electrode). This is 50 mV higher than that of FePc supported on graphene and 64 mV higher than that of Pt/C in 0.1 m KOH solution at a catalyst loading of 0.1 mg cm −2 . X‐ray absorption spectroscopy and electrochemical cyclic voltammetry results indicate that the incorporated FeO x NCs interact with the active center of FePc, Fe−N4, to enhance the electron transition and reversibility of the Fe III /Fe II redox couple and promote the kinetics of the ORR. We demonstrate that the nature of the active center of FePc (i.e., Fe−N4 ) is related closely to the activity of the Fe III /Fe II redox couple. Abstract : Size matters : We synthesize FeO x nanoclusters (NCs) incorporated with iron phthalocyanine (FePc) supported on graphene (FeO x /FePc) as highly active electrocatalysts for the oxygen reduction reaction by a self‐assembly method. The electrochemical activity of FeO x /FePc depends on the loading or size of the FeO x NCs. The best results are obtained on FeO x /FePc with 10 wt % FeO x NCs of a size of approximately 2 nm and a thickness of approximately 0.6 nm.